Respostas

A melhor resposta!
2014-06-17T09:10:03-03:00
(x-6).(x-2)=21
x^{2}-2x+12-6x=21
x^{2}-8x+12-21=0
x^{2}-8x-9=0
x^{2}-8x+4^{2}=9+4^{2}
(x-4)^{2}=25
x-4=+/- \sqrt{25}

x'=4+5
x'=9

x''=4-5
x''=-1

Substituindo temos:

x'-6 ⇒ 9-6 ⇒ 3
x'-2 ⇒ 9-2 ⇒ 7

ou

x''-6 ⇒ -1-6 ⇒ -7
x''-2 ⇒ -1-2 ⇒ -3

Como não existe tamanho negativo as dimensões do retângulo são: 7x3
3 5 3
(x-6).(x-2)=21
x^{2}-2x+12-6x=21
x^{2}-8x+12-21=0
x^{2}-8x-9=0
x^{2}-8x+4^{2}=9+4^{2}
(x-4)^{2}=25
x-4=+/- \sqrt{25}

x'=4+5
x'=9

x''=4-5
x''=-1

Substituindo temos:

x'-6 ⇒ 9-6 ⇒ 3
x'-2 ⇒ 9-2 ⇒ 7

ou

x''-6 ⇒ -1-6 ⇒ -7
x''-2 ⇒ -1-2 ⇒ -3